2021
DOI: 10.1111/ijcs.12700
|View full text |Cite
|
Sign up to set email alerts
|

Hope, fear, and consumer behavioral change amid COVID‐19: Application of protection motivation theory

Abstract: Using protection motivation theory (PMT), this study investigates the influence of cognitive assessment and affective response on customers’ behavioral intention amid COVID‐19 in the context of restaurants. More specifically, this research draws attention to (1) the influence of protection motivation (i.e., perceived vulnerability, perceived severity, maladaptive reward, response efficacy, self‐efficacy, response cost) on hope and fear, (2) hope and fear as mediators between protection motivation and behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
182
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(217 citation statements)
references
References 62 publications
9
182
1
Order By: Relevance
“…While several studies reported strengthening of environmental motivation (e.g., O'Connor & Assaker, 2021 ; Schiller et al, 2021 ), other studies found no effect of the crisis on environmental motivation (e.g., Lucarelli et al, 2020 ; Rousseau & Deschacht, 2020 ; Čadová, 2020 ). Correspondingly, some studies reported increased (intention to) pro-environmental behaviors (e.g., recycling and waste handling, sustainable food consumption, and sustainable travel behavior; Kim et al, 2021 ; O'Connor & Assaker, 2021 ; Tchetchik et al, 2021 ), whereas other studies reported increased environmentally harmful behavior (e.g., an increase in the use of plastic products; Prata et al, 2020 ).…”
mentioning
confidence: 99%
“…While several studies reported strengthening of environmental motivation (e.g., O'Connor & Assaker, 2021 ; Schiller et al, 2021 ), other studies found no effect of the crisis on environmental motivation (e.g., Lucarelli et al, 2020 ; Rousseau & Deschacht, 2020 ; Čadová, 2020 ). Correspondingly, some studies reported increased (intention to) pro-environmental behaviors (e.g., recycling and waste handling, sustainable food consumption, and sustainable travel behavior; Kim et al, 2021 ; O'Connor & Assaker, 2021 ; Tchetchik et al, 2021 ), whereas other studies reported increased environmentally harmful behavior (e.g., an increase in the use of plastic products; Prata et al, 2020 ).…”
mentioning
confidence: 99%
“…Businesses have experienced substantial growth in their online customer base since the start of the pandemic, of which the markets with existing high conversion rates continue to grow [48]. This sudden adversity towards shopping in physical stores might be caused by cognitive responses to the COVID-19 pandemic, i.e., fear and hope [8]. These factors have been found to mediate the relationship between a consumer's ability to cognitively assess the threat and their behavior [8]; hence, those who experience high levels of fear and perceive the situation to be very threatening will stay home and do their shopping online.…”
Section: The Effect Of Covid-19 On Consumer Behavior and Businessesmentioning
confidence: 99%
“…This sudden adversity towards shopping in physical stores might be caused by cognitive responses to the COVID-19 pandemic, i.e., fear and hope [8]. These factors have been found to mediate the relationship between a consumer's ability to cognitively assess the threat and their behavior [8]; hence, those who experience high levels of fear and perceive the situation to be very threatening will stay home and do their shopping online. Although many consumers indicate that they will most likely continue to shop online, even after stores reopen [49,50], consumer who prefer shopping in physical stores are also forced to adapt to online shopping [10].…”
Section: The Effect Of Covid-19 On Consumer Behavior and Businessesmentioning
confidence: 99%
See 2 more Smart Citations